FORMULASI TEPUNG KOMPOSIT UMBI JALAR DAN TALAS SEBAGAI SUBSTITUSI PARSIAL TERIGU PADA CAKE - Healthy Aldriany Prasetyo; Lyndon Parulian Nainggolan (Universitas Quality, 2018)
The research was aimed to formulation combination of composite flour as partly substitution of wheat flour from blend of wheat flour, sweet potato flour and taro flour. This research used a Completely Randomized Design (CRD) Non Factorial, with different level of substitution in percents, i.e :T1 = wheat flour (100%), T2 = wheat flour (75%) : sweet potato flour (25%), T3 = wheat flour (50%) : sweet potato flour (50%), T4 = wheat flour (25%) : sweet potato flour (75%), T5 = wheat flour (75%) : taro flour (25%), T6 = wheat flour (50%) : taro flour (50%), T7 = wheat flour (25%) : taro flour (75%). The parameters analysed were moisture content, ash content, protein content, fat content,carbohydrate content and hedonic value of colour, aroma, flavour and texture. The results showed were significant differences (p<0.5) difference formulation combination of composite flour with different level of substitution. The proximate composition showed that wheat flour had higher protein content (9.46%) and lower carbohydrate content (87.77%), while sweet potato flour had protein content(3.96%) and carbohydrate content (92.92%); taro flour had protein (5.62%) and carbohydrate content (92.83%). The sensory analysis of cake showed significant differences between 100% wheat flour and formulation combination of composite flour samples. It was concluded that formulation composite flour T4 into wheat flour gave the cake with the best overall quality acceptabily.